Internal and External Perspectives on Quality of Healthcare Services at Sanglah General Hospital Denpasar - Made Nopy Diah Sundari; Putu Ayu Indrayathi; Raden Ayu Tuty Kuswardhani (Universitas Udayana, 2014)
Background and purpose: Customer satisfaction is a primary indicator of the quality of public healthcare services. This study investigated internal (hospital staff) and external (hospital clients) perspectives in order to gain insight into the quality of care at Sanglah General Hospital. Methods: The study used both qualitative and quantitative methodologies with 11 informants and 106 respondents. Qualitative data obtained through in-depth interviews with hospital staff were analyzed thematically. Quantitative data obtained through self-administered questionnaire were analyzed using univariate analysis. Results: Informants from the qualitative data collection stated that Sanglah General Hospital has a relatively high level of service and that existing structures to mitigate issues are in place, which act as reinforcing factors. Data from the quantitative survey indicated that clients were satisfied with the quality of service (ServQual), with an overall percentage of 83.82%. Conclusion: Further efforts could be made in order to improve healthcare provision at Sanglah Hospital, particularly from the perspective of hospital facilities, staff support and increased implementation of clinical governance.